New Ethiopian Ministry of Agriculture data sharing policy supported by WLE/CIAT and GIZ to improve food production while building landscape health - CGIAR Research Program on Water, Land and Ecosystems (2019)
WLE/CIAT, Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) and partners supported the Ethiopian Ministry of Agriculture to adopt a comprehensive data sharing policy. Currently, data sets, for example fertility trials, are scattered among many scientists and institutions, severely limiting the ability to target fertilizer recommendations to farmers. This will now change as the Ministry is working with stakeholders to collate datasets to develop national fertilizer recommendations. This policy will undoubtedly support the agricultural transformation agenda.